Kontribusi Faktor Budaya Dan Agama Terhadap Upaya Moderasi Beragama Di Maluku:: Kajian Historisitas-Deskriptif - Rahawarin, Bernard A. (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2024)
This article aims to describe the historical experience of cultural and religious affirmation and negation in the context of efforts to promote religious moderation in Maluku. Historical data on cultural and religious diversity were gathered using a literature study method. The attempt to build national unity through interreligious tolerance has long been pursued and is now known as religious moderation. The promotion of religious moderation in Maluku is constantly influenced by the cultural and religious backgrounds of community members. Through an analysis of the collected historical facts, this article successfully identifies how culture and religion contribute to the efforts to promote religious moderation in Maluku. These contributions are reflected in the forms of affirmation and negation.